(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The global education industry has recently experienced immense development. Demand for new academic disciplines has increased as a result of globalization and the digital revolution. Better teaching strategies and tools have increased the cost of providing education. Only institutions that offer their students a high-quality education and a supportive environment will succeed in this competitive market. The amount of experiences and perceived performance of educational services during their study period determines how satisfied students are with their education. Accordingly, an effort has been made to study the student satisfaction with the educational service offered by Nagaon Gopinath Dev Goswami Commerce College in the Nagaon District of India. The degree to which students are satisfied with the educational services is assessed in this study.